Detrital record of initial basement exhumation along the Laramide deformation front, southern Rocky Mountains. Issue 9 (24th September 2016) - Bush, Meredith A.; Horton, Brian K.; Murphy, Michael A.; Stockli, Daniel F.
Abstract: New geochronological constraints on upper crustal exhumation in the southern Rocky Mountains help delineate the latest Cretaceous–Paleogene history of drainage reorganization and landscape evolution during Laramide flat‐slab subduction beneath western North America. Detrital zircon U‐Pb results for the Raton basin of southern Colorado and northern New Mexico define the inception of coarse‐grained siliciclastic sedimentation and a distinctive shift in provenance, from distal to proximal sources, that recorded shortening‐related uplift and unroofing along the Laramide deformation front of the northern Sangre de Cristo Mountains. This Maastrichtian–early Paleocene (~70–65 Ma) change—from distal foreland accumulation of sediment derived from the thin‐skinned Cordilleran (Sevier) fold‐thrust belt to coarse‐grained sedimentation proximal to a Laramide basement block uplift—reflects cratonward (eastward) deformation advance and reorganization of drainage systems that supplied a large volume of Paleocene–lower Eocene sediments to the Gulf of Mexico. The timing of unroofing along the eastern deformation front is synchronous with basement‐involved shortening across the interior of the Laramide province, suggesting abrupt wholesale uplift rather than a systematic inboard advance of deformation. The growth and infilling of broken foreland basins within the interior and margins of the Laramide province had a significant impact on continental‐scale drainage systems, as several ponded/axial Laramide basins trapped large volumes of sediment and induced reorganization of major source‐to‐sink sediment pathways. Key Points: The Raton basin of Colorado and New Mexico records Laramide deformation and partitioning of the Cordilleran foreland basin Provenance results for Maastrichtian Vermejo and Raton Formations show early basement exhumation related to Laramide shortening Paleocene uplift of the Sangre de Cristo range formed a topographic barrier, blocking western sources from contributing to the Raton basin